"It's not like this here": teaching a Youth Lens in South Korea. Issue 3 (10th June 2020) - Murfield, Ryan
Abstract : Purpose: This paper aims to identify challenges in a first attempt at teaching the Youth Lens in a secondary English classroom in South Korea. Design/methodology/approach: This paper includes the author's observations of a senior English class in an international school in South Korea. Findings: The author advocates that intersections of time, geography and culture have a significant influence that cannot be ignored when teaching about adolescence. Additionally, when bringing a Youth Lens into the classroom teachers need to be prepared to fully embrace its embedded questions of power between youth and adults. Originality/value: This paper extends existing academic conversation on a Youth Lens to include both an international setting and instances in which the teacher is not of the majority demographic in the classroom.